Effect of ELF-EMF on K562 cell differentiation in the presence or absence of quercetin and heat-shock - GARİP, GÜNSELİ AYŞE (TAYLOR & FRANCIS LTD, 2007)
Extremely low frequency electromagnetic fields (ELF-EMF) are known to produce a variety of biological effects although the underlying mechanism has not been elucidated yet. The present study aimed to investigate the effect of ELF-EMF on K562 cells induced to differentiate with or without quercetin with application of heat-shock. 50Hz ELF-EW was applied at three (1mT,5mT,10mT) field intensities. Quercetin is,flavonoid known to have anti-tumorigenic and anti-proliferative properties. Heat-shock was applied since it has been shown that quercetin down-regulates but ELF-EMF increases heat-shock protein levels. Results of this study show that ELF-EMF increases differentiation of untreated K562 cells at low field intensities in accordance with the window effect of these fields. Heat-shock abolishes this increase. Heat-shock also decreases the %differentiation of quercetin induced cells. However it has no effect on quercetin induced ELF-EMF exposed cells implying a protective effect of ELF-EMF These results prompted us to hypothesize that these fields can act antagonistically with heat-shock under certain conditions.
Keywords: ELF-EMF; quercetin; heat-shock; differentiation; K562; GENE-EXPRESSION; FLAVONOIDS; INDUCTION